Eine empirische Analyse der Spreadunterschiede von Festsatzanleihen zu Floatern im Euroraum und deren Zusammenhang zum Preis eines Credit Default Swaps - Thomas Heidorn; Jens Kantwill (Hochschule für Bankwirtschaft (HfB), 2002)
The paper analyses the factors influencing the credit spread of exteuro denominated bonds and credit default swaps. The regression shows a significant difference of the credit spread of corporate floaters compared to straight bonds. The steepnes of the yield curve leads surprisingly to lower credit spreads. This is also true for a higher risk free rate. The liquidity effect matters for straight bonds but is unimportant for floaters. The rating has a significant influence, but can only partially explain the spread. It can be shown that the same factors influence the spread of a credit default swap. As predicted by theory the floater spread has an almost linear relationship to the CDS Spread, but it can only explain 50% of its movement, because transaction prices and different liquidity play a substantial role in pricing these products.
urn:nbn:de:101:1-2008071837
Keywords: 330; Credit Spread; Risikoaufschlag von Anleihen; Fix-Float Spread; Bewertung von CDS; Pricing of Credit Default Swaps